Neural Advantages of Older Musicians Involve the Cerebellum: Implications for Healthy Aging Through Lifelong Musical Instrument Training - Yamashita, Masatoshi; Ohsawa, Chie; Suzuki, Maki; Guo, Xia; Sadakata, Makiko; Otsuka, Yuki; Asano, Kohei; Abe, Nobuhito; Sekiyama, Kaoru (Frontiers in Human Neuroscience, 2022)
This study compared 30 older musicians and 30 age-matched non-musicians to investigate the association between lifelong musical instrument training and age-related cognitive decline and brain atrophy (musicians: mean age 70.8 years, music playing 52.7 years; non-musicians: mean age 71.4 years, no or less than 3 years of musical training). Although previous research has demonstrated that young musicians have larger gray matter volume (GMV) in the auditory-motor cortices and cerebellum than non-musicians, little is known about older musicians. Music imagery in young musicians is also known to share a neural underpinning (the supramarginal gyrus and cerebellum) with music performance. Thus, we hypothesized that older musicians would show superiority to non-musicians in some of the abovementioned brain regions. Behavioral performance, GMV, and brain activity, including functional connectivity during melodic working memory tasks, were evaluated in both groups. Behaviorally, musicians exhibited a much higher tapping speed than non-musicians, and tapping speed was correlated with executive function in musicians. Structural analyses revealed larger GMVs in both sides of the cerebellum of musicians, and importantly, this was maintained until very old age. Task-related functional connectivity analyses revealed that musicians possessed greater cerebellar-hippocampal functional connectivity, which was correlated with tapping speed. Furthermore, musicians showed higher activation in the supramarginal gyrus during melodic working memory tasks; this was correlated with earlier commencement of instrumental training. These results indicate advantages or heightened coupling in brain regions associated with music performance and imagery in musicians. We suggest that lifelong instrumental training highly predict the structural maintenance of the cerebellum and related cognitive maintenance in old age.